A Comparative Study between the Effects of Intra-Articular Injections of Platelet Rich Plasma versus Corticosteroid with Local Anaesthetic in Refractory Cases of Temporo-Mandibular joint Disorder- A Comparative Study - Madhumita Batabyal; Indranil Sen; Rabi Hembrom; Pradip Kumar Ray; Arijit Nag; Kapil Bala; Jayanta Barman; Anamika Anamika (Bengal Journal of Otolaryngology and Head Neck Surgery)
Abstract: